Potential of Pedada Fruit as A Renewable Energy and Climate Mitigation Source in Indonesia: A Review - Ningrum, Sari Sekar; Angeline, Annisa Yuliana; Ardani, Muhamad Sofi; Shadiq, Zhilal (Journal of Community Based Environmental Engineering and Management, 2026)
Indonesia has one of the largest mangrove ecosystems in the world, which provides important ecological functions such as coastal protection, biodiversity support, and climate mitigation. Among various mangrove species, Sonneratia sp. (pedada fruit) has attracted attention due to its high carbohydrate content, making it a promising biomass source for renewable energy production. This study aims to evaluate the potential of pedada fruit as a raw material for bioethanol production and its contribution to climate change mitigation in Indonesia through a comprehensive literature review. This review analyzed approximately 50 scientific articles, conference proceedings, and research reports related to mangrove biomass utilization, bioethanol production processes, and the environmental benefits of mangrove ecosystems. The results showed that pedada fruit contains approximately 59% carbohydrates along with lignocellulosic components such as cellulose, lignin, and hemicellulose, which are suitable for conversion into bioethanol through pretreatment, hydrolysis, fermentation, and distillation processes, and can be applied in Indonesia with its large number of mangroves. Bioethanol production from mangrove fruit can follow second- to fourth-generation bioethanol technologies, depending on the processing approach used. In addition to providing renewable energy, utilizing mangrove fruit as a bioethanol feedstock can encourage community participation in mangrove conservation and restoration efforts. Therefore, mangrove fruit has significant potential as a sustainable, renewable energy source while also supporting climate mitigation strategies and coastal ecosystem management in Indonesia.